Orthopedic Injury Diagnosis Using Digital Radiography: A Retrospective Study - Nadia Khattak, Kalsoom Nawab, Sadaf Naveed, Hina Gul, Naheed Khan, Irsa Shoaib, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Hundred patients were examined to determine the effectiveness of digital radiography in detecting Orthopedic injuries. The decisive findings showed that digital radiography was quite efficient, with a 91% diagnostic success rate. As a result, digital radiography is an effective and cost-effective method for identifying Orthopedic injuries. Aim: The comparison of digital radiography with other Orthopedic imaging modalities is intended to ascertain how well it can diagnose injuries and how much it costs. figuring out the factors that determine how accurate it is at detecting Orthopedic injuries. Methods: We did a retrospective analysis at the radiology department of the Khyber Teaching Hospital in Peshawar from Feb 2016 to Feb 2017. The medical files and radiographic pictures of hundred individuals who underwent digital radiography for orthopedic injuries were the subject of our study. In the course of our investigation, we also gathered demographic information including age and sex. Two radiologists separately analysed the radiography pictures to get the most reliable findings. The agreement between the final diagnoses provided by the attending Orthopedic surgeon and the radiologists was our definition of accurate diagnosis. Finally, we evaluated how much the digital radiography would cost. Results: Comparing digital radiography to more expensive imaging techniques like CT and MRI revealed considerable cost reductions. [91%] of the patients received the right diagnosis after the use of digital radiography. Results were inconclusive or incorrect for the remaining [9%]. Conclusion: This research found that the diagnosis of Orthopedic injuries using digital radiography was both economical and accurate. The accuracy rate was satisfactory, with patient correct diagnostic rates of[ 91%]. In addition, compared to other imaging methods, digital radiography was much less expensive. Keywords: Orthopedic injuries, diagnosis, accuracy, cost-effectiveness, digital radiography